The marketing strategy: A Case Stduy OF CHINA Unicom - Yajid, Mohd Shukri Ab; Shukri, Shakeerah Mohd; Khatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The prime of is to examine the marketing strategies in the Unicom industry of China. Over the past three years, China has added over 312 million mobile subscribers to overtake the US. China Unicom Limited (China United telecommunication Corporation), with more than 35% of china’s 312 million subscribers at the end of the December 2004, is the second largest operator in China market. Due to the large part to access to capital and a regulatory that allows it preferential pricing, the issuance of additional license 3G license and the impact of China became a member of the world Trade Organization (WTO) will transform the competitive landscape in telecommunication market. China Unicom now operates the largest CDMA network in the world with subscribers spread over widely diverse market conditions. In the past three years, CDMA’s performance is under the expectation. How well prepared is China Unicom management to assure continued growth in this new environment? How does China Unicom to convert CDMA market position. The findings exposed that there are many factors are affecting positively as well negatively to the market strategies related to the Unicom in China.